Drugs to reduce bleeding and transfusion in adults undergoing cardiac surgery: A systematic review and network meta analysis - Beverly, A; Ong, G; Wilkinson, K; Doree, C; Welton, N; Estcourt, L (Cochrane Collaboration, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy and safety of haemostatic drugs (including antifibrinolytics) and topical agents for reducing bleeding, transfusion, and reoperation in adults undergoing cardiac surgery.